Vertical Integration of the Rice Market in Lampung Province - Nazilah, Nazilah; Noer, Irmayani; Kurniawan, Henry (Journal of International Conference Proceedings, 2024)
Rice prices in Indonesia rose significantly in early 2024, with premium-quality rice reaching IDR 16,410 per kilogram—a 21.3% increase compared to the previous year. These disparities stem from weaknesses in the agribusiness structure, poor market integration, and insufficient market information. This study aims to analyze rice market integration at the farmer-producer and consumer levels in Lampung Province. Secondary time-series data on grain prices at the producer level and retail rice prices at the consumer level from 2018 to 2023 were analyzed using price correlation, price transmission elasticity, and the IMC method. Results indicate a consistent upward trend in both retail rice and farmers’ grain prices, which are positively correlated. However, price transmission elasticity reveals that price changes at the farmer-producer level outpace those at the consumer level. The analysis concludes that rice market integration in Lampung is weak in the short term but demonstrates strong integration over the long term. These findings highlight the need for improved agribusiness structures and better market information systems to enhance market efficiency